2022
DOI: 10.1111/imj.15687
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisation and associated costs of gastrointestinal bleeding from primary prevention aspirin use in South Australia: a retrospective case series analysis

Abstract: We assessed hospitalisations for gastrointestinal bleeding directly related to primary prevention aspirin in lower risk patients for a 6-month period in three South Australian hospitals. Those with related underlying pathology or concurrent causative medication were excluded. Identified patients (n = 22) carried little co-morbidity, 41% received prior proton-pump inhibitors and 68% were aged >70 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“… 42 Cost of hysterectomy AU$12,124 ±25% Gamma Lynch Syndrome Australia 19 Cost per gastrointestinal bleeding hospitalisation AU$60,769 ±25% Gamma Roberts et al. 57 Utility weight CRC 0.76 0.699–0.823 Beta Farlikka et al. 58 Utility weight post-CRC health state 0.85 ±16% (SD) Beta Mulder et al.…”
Section: Methodsmentioning
confidence: 99%
“… 42 Cost of hysterectomy AU$12,124 ±25% Gamma Lynch Syndrome Australia 19 Cost per gastrointestinal bleeding hospitalisation AU$60,769 ±25% Gamma Roberts et al. 57 Utility weight CRC 0.76 0.699–0.823 Beta Farlikka et al. 58 Utility weight post-CRC health state 0.85 ±16% (SD) Beta Mulder et al.…”
Section: Methodsmentioning
confidence: 99%
“…In this journal, three recent independent studies from three states in Australia reported that most non-variceal UGIB episodes in those aged ≥70 years are attributable to low-dose aspirin use. [18][19][20] First, among people aged ≥70 years admitted with UGIB to a Western Australian tertiary hospital, those taking regular low-dose aspirin had a nine-fold increased risk of presentation with overt UGIB characterised by haematemesis and/or melaena compared with those not taking aspirin. 18 Three-quarters of older people with UGIB had been taking aspirin.…”
mentioning
confidence: 99%
“…19 In the third study, Roberts et al found increased risk of UGIB associated with aspirin used for primary prophylaxis in adults with mean age 70 years in a three-hospital South Australian Study. 20 The mean cost of hospitalisation with UGIB was estimated as A$6769. Extrapolating this cost to the 25 727 people aged ≥70 years from the AIHW data provides an annual estimate of hospitalisation costs of over $AU170 million in older people with gastroduodenal ulcers.…”
mentioning
confidence: 99%
See 2 more Smart Citations